Antimicrobial screening and hemolytic activity of products obtained from Piper montealegreanum Yuncker and effect in vitro on growth of Staphylococcus aureus (Research, Society and Development, 2020)
This study aimed to determine spectrum of antimicrobial activity of crude ethanolic extract (CEE), chloroform (CHCl3) and ethyl acetate (EtOAc) fractions, to determine influence of CHCl3 fraction on Staphylococcus aureus growth and hemolytic activity. Antimicrobial screening of CEE, CHCl3 and EtOAc fractions was carried out using broth microdilution technique against standard strains: Staphyloccocus aureus ATCC25923, Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853 and Candida albicans ATCC76645 to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Time kill curves were performed to determine influence of CHCl3 fraction on MIC and ½ MIC concentrations on S. aureus growth. Hemolytic activity of CHCl3 was performed in human erythrocytes to report the cytotoxic effect. CHCl3 fraction showed activity against S. aureus with MIC=1024 µg mL-1 and MBC=2048 µg mL-1. This fraction did not show activity against other tested strains, as well as the CEE and EtOAc fraction. Time kill curve of S. aureus treated with CHCl3 fraction showed that at MIC this fraction has bacteriostatic activity, which was not observed with the ½ MIC. Hemolytic activity demonstrated that when CHCl3 fraction in MIC does not present membrane damage of erythrocytes, since it did not cause hemolysis. Studies should be conducted to evaluate the activity of CHCl3 fraction against S. aureus with different antimicrobial resistance profiles, in addition to evaluating the potential for resistance reversion by in vitro combination studies. The study demonstrated that the species P. montealegreanum can be an important source of compounds of importance for combating microorganisms of clinical importance.